The role of p38 MAPK in the induction of intestinal inflammation by dietary oxysterols: modulation by wine phenolics. Issue 4 (4th March 2015) - Guina, Tina; Deiana, Monica; Calfapietra, Simone; Cabboi, Barbara; Maina, Marco; Tuberoso, Carlo I.; Leonarduzzi, Gabriella; Gamba, Paola; Gargiulo, Simona; Testa, Gabriella; Poli, Giuseppe; Biasi, Fiorella
Abstract : Dietary oxysterols promote intestinal inflammation mainly through NOX1/p38 MAPK/NF-κB signaling axis. Specific wine phenolics target each branch of this axis. Abstract : Dietary oxysterols are cholesterol auto-oxidation products widely present in cholesterol-rich foods. They are thought to affect the intestinal barrier function, playing a role in gut inflammation. This study has characterized specific cell signals that are up-regulated in differentiated CaCo-2 colonic epithelial cells by a mixture of oxysterols representative of a hyper-cholesterolemic diet. p38 MAPK activation plays a major role, while other signal branches, i.e. the JNK and ERK pathways, make minor contributions to the intestinal inflammation induced by dietary oxysterols. p38 transduction might be the missing link connecting the known NADPH oxidase activation, and the induction of NF-κB-dependent inflammatory events related to oxysterols' action in the intestine. A NOX1/p38 MAPK/NF-κB signaling axis was demonstrated by the quenched inflammation observed on blocking individual branches of this signal with specific chemical inhibitors. Furthermore, all these signaling sites were prevented when CaCo-2 cells were pre-incubated with phenolic compounds extracted from selected wines made of typical Sardinian grape varieties: red Cannonau and white Vermentino. Notably, Cannonau was more effective than Vermentino. The effect of Sardinian wine extracts on intestinal inflammation induced by dietary oxysterols might mainly be due to their phenolic content, more abundant in Cannonau than in Vermentino. Furthermore, among different phenolic components of both wines, epicatechin and caffeic acid exerted the strongest effects. These findings show a major role of the NOX1/p38 MAPK/NF-κB signaling axis in the activation of oxysterol-dependent intestinal inflammation, and confirm the concept that phenolics act as modulators at different sites of pro-oxidant and pro-inflammatory cell signals.